TETRACYCLINE MOUTHWASH AS ORAL CAVITY ULCER THERAPY IN PATIENTS WITH A HISTORY OF ALLERGIES - Cane Lukisari; Dwi Setyaningtyas; Nafi’ah Nafi’ah; Maharani Laillyza Apriasari (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: One of the allergic reactions in the oral mucosa is ulceration caused by IgE-mediated reactions to food substances or non-IgE-mediated reactions and non-immunological mechanisms. Ulceration is a damage to the epithelium of the oral cavity that affects the nerve endings in the lamina propria layer so that it causes pain or heat that requires treatment and therapy. Objective: To report the occurrence of ulcers due to food allergies and therapy with tetracycline mouthwash 0.25% solution. Case: A 22-year-old female patient came with complaints of a small ulcer on the inside of the gums and the entire upper and lower lips and a numb and dry tongue. The patient always experiences an ulcer every time he eats seafood and certain foods that the patient cannot mention because it happens so often and every time an ulcer appears it will continue to get bigger. Management: Patients are advised to avoid allergens and refer for a complete blood allergy test and Ig E. Tetracycline mouthwash 0.25% solution was given to be rinsed three times a day. And added supportive therapy, giving multivitamins. Conclusion: Tetracycline mouthwash has antimicrobial properties and properties as inhibitors of tissue metalloproteinases (TIMPs) can accelerate healing time and ulceration does not continue to get bigger, reduce taste and pain, according to the theory it can reduce secondary speed limits and duration. inhibits collagenase. Keyword: Allergy, Mouthwash, Tetracycline, Ulcer